Spiritual inclusiveness at end-of-life for Punjabi Indians: experience with Regional Residential Aged Care Facilities. Issue 2 (3rd April 2021) - Wardle, Sabine; Bennett, Cary
ABSTRACT: This article draws on data generated from a wider study into experiences of the Punjabi Indians with palliative care services at regional residential aged care facilities (RACFs) in the Riverina region of New South Wales (NSW) Australia. Using a qualitative phenomenological approach, group interviews with the Punjabi Indians and the care staff of RACFs reveal a perceived substandard quality of psychosocial care, one that overlooks religious and spiritual aspects for service users. The findings of this study highlight the importance of restoring the balance between biomedical and psychosocial-spiritual aspects of palliative care especially for culturally and linguistically diverse (CALD) and faith groups, such as Punjabi Indians within the aged care sector.